Organisasi Profesi Jurnalis dan Kode Etik Jurnalistik - Sulistyowati, Fadjarini (Jurnal ILMU KOMUNIKASI, 2006)
Abstract: If managed professionally, the function of the press will be maximum. A professionalism press will always keep the quality of the news, and this is depend on the capability of the journalist. A good journalist upholds the quality of the news and used it as an indicator whether the press function works well or not. It is because a good journalist will be very obedience to the application of the ethics code of his profession. To keep the journalistic code of ethics works, it is necessary to have a journalist organization. This organization of journalist profession to increase the press professionalism to the commitment to control the journalistic code of ethics.